Electrocatalytic Properties of a Gold Nanoseed Particle‐modified Indium Tin Oxide Electrode: Comparison of the Shape and Preparation Methods. Issue 5 (8th January 2016) - Aziz, Md. Abdul; Sohail, Manzar; Shaikh, M. Nasiruzzaman; Oyama, Munetaka
Abstract: Gold nanostructures are the most commonly used nanostructures for fabricating electrochemical sensors and biosensors. In this study, we compared the catalytic performances of three types of gold nanoseed particles having two different morphologies, upon attachment to an amino‐functionalized ITO electrode surface. The ITO electrode surface was modified with 3‐aminopropyltrimethoxysilane (APTMS) and (1) gold nanoseed spheres (AuNSS), prepared using the ion capture and successive reduction method (ICR), (2) commercially available 5 nm AuNSS, and (3) a newly synthesized gold nanoseed wire (AuNSW). The electrocatalytic properties of the three electrodes were evaluated. Among the three electrodes, the AuNSW/APTMS/ITO was found to be the electrode of choice and exhibited excellent electrocatalytic properties toward the biologically important analytes glucose, uric acid, and serotonin. Abstract :